Kebijakan Fiskal, Moneter Dan Neraca Pembayaran Di Indonesia: Suatu Kajian Efektifitas - Alpon Satrianto (Economac: Jurnal Ilmiah Ilmu Ekonomi, 2017)
This study is based on the long debate that occurs among economists about the effectiveness of fiscal and monetary policy on the output of a country. Some economists argue that fiscal policy is more effective against the output of a country while others argue that monetary policy is more effective. However, the economist's debate only sees the effectiveness of fiscal and monetary policy on output. No such economist sees the effectiveness of fiscal and monetary policy on other macroeconomic variables such as balance of payment. Therefore, this study contributes to analyzing the most effective policies on balance of payment in Indonesia. This study uses time series data from 1970-2015. Fiscal policy data is measured from real government expenditure, monetary policy is measured from real money supply, and balance of payment is measured from the overall balance sheet value. Data analysis techniques use Vector Auto Regressive (VAR), Impulse Response Function (IRF) and Forecast Error Variance Decomposition (FEVD). A policy is said to be effective if the FEVD method shocks one policy against output variability and the price is greatest compared to other policies. The results conclude that fiscal policy is more effective on balance of payment than monetary policy. This is evident from the shock of fiscal policy based on FEVD method is the most important role to the variability of balance of payment in Indonesia when compared with fiscal policy. With the word meaning, fiscal policy has a big role to the changes that occur in the balance of payment in Indonesia.